EFFORTS TO IMPROVE BASIC MOVEMENT OF SHORT DISTANCE RUNNING USING DEMONSTRATION METHOD IN CLASS V SD NEGERI 62 KOTA BENGKULU - Reza Kurnia Sandi; Tito Parta Wibowo (Hanoman Journal: Physical Education and Sport, 2020)
This study aims to determine the improvement   in the basic motion skills of short- distance sprint through sports learning  by the application of demonstration methods to fifth grade students at SD Negeri 62 Bengkulu City. The method used in this study was a class action research method. The population in this study were fifth grade students at SD Negeri 62 Bengkulu City. Number of Samples were 20 students. The instrument in this study was an observation sheet on student’s attitudes while measuring the basic motion skills of short-distance sprint , the researcher used a 30 Meter short-distance sprint practice test. Based on the results, it was found that there was an improvement in the basic motion skills of short-distance sprint of fifth grade students at SD Negeri 62 Bengkulu City through the application of demonstration methods. In the pre-cycle showed a minimum completeness percentage of 0%  students who completed above the KKM average value, while in the cycle I obtained a minimum percentage of completeness of 45% students above the KKM value, and in the second cycle obtained a minimum percentage of completeness of 85%  students above the KKM average. From the results of this study, it can be concluded that the application of the demonstration method can improve the basic motion skills of short-distance sprint in fifth grade students in fifth grade students at SD Negeri 62 Bengkulu City.